The dentin surface of the root canal comparative characteristics during decontamination with a diode laser, depending on the irrigation solution (Эндодонтия Today)
At present, there are a large number of methods and tools for the root canal system qualitative biomechanical instrumental processing. To remove tissue degradation, lubricated layer and disinfect the root canal system the laser radiation is used being one of the modern technologies that are currently applied in endodontic practice. The our study purpose was to assess the state of the root canal dentin surface after its treatment with a diode laser, depending on the dental irrigation solutions used in endodontic treatment. With the help of scanning electron microscopy, the root canals dentin surface of the removed teeth was examined after treatment with a diode laser. As a result, it was found that the diode laser using does not damage the dentin surface, facilitates the lubricated layer removal, improves the conditions for the adhesion of syllables and, accordingly, improves the endodontic treatment quality.